2014
DOI: 10.1016/j.chemosphere.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins levels in breast milk of women living in Caserta and Naples : Assessment of environmental risk factors

Abstract: Naples and Caserta provinces are extensively affected by the illegal dumping of hazardous and urban wastes, which were periodically set to fire. Several studies were made on the possible health impact of this illegal waste management. The aim of the study was to detect dioxins levels in breast milk of volunteer primiparae and to assess the possible source of dioxins in the affected areas. The authors determined dioxins levels in breast milk from 100 primiparae from the study area and collected anamnestic infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…In this context we have explored the expression of CYP1A1 in the acne lesions of 16 patients living in the region of Naples, Italy, where different epidemiological studies suggest an environmental contamination by dioxins [16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…In this context we have explored the expression of CYP1A1 in the acne lesions of 16 patients living in the region of Naples, Italy, where different epidemiological studies suggest an environmental contamination by dioxins [16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides known chloracnegens from the dioxin‐like family, a great variety of compounds may activate the AhR‐dependent signalling pathway. In our project to analyse the dermal cysts of patients presenting such a clinical pattern, we found CYP1A1 expression in patients living in areas submitted to the fumes of pollutant waste incinerators, or close to public dumps . Other patients may have been exposed to various chemical during their professional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [32, 33] regarded areas in which biomonitoring detected presence of dioxins in breast milk of women [34]. In the latter studies the synergistic effects between different risk factors, including B hepatitis virus and hazardous waste contaminants, may be reasonably hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals in soil and groundwater, and β-HCH in blood of some residents were reported in the Sacco river areas [31]; hexachlorocyclohexanes, benzylchlorides, organic sulfur compounds, chlorobenzenes, and sodium sulfide/sulfhydrates polluted the Love Canal site [36], where a biomonitoring study reported also trichlorobenzene and dichlorobenzene contamination [37]. Dioxins were detected in biomonitoring studies in Campania waste sites [34] located in towns where increased bladder cancer risk was reported [32, 33]. …”
Section: Discussionmentioning
confidence: 99%